Intervention programme to improve emotional regulation among adolescent with mental disorders: a systematic review - Kholifah, Siti; Khuzaimah Ahmad Sharoni, Siti; Yusuf, Ah (International Journal of Public Health Science (IJPHS), 2024)
Adolescence is an important period for developing social and emotional habits that are important for mental well-being. This research aimed to know the effectiveness of intervention programs to improve emotional regulation in adolescents with mental disorders. Preparation using the PICO approach, determination of inclusion and exclusion criteria, and a literature review of scientific English articles published between 2016 and 2023 were conducted. Data were obtained from the SCOPUS, Science Direct, SpringerLink, ProQuest, and SAGE databases. Assessment of the title, abstract, and full text of the article with the keywords "Adolescent," "Child," "Teenager," "Emotion regulation," "Emotion exposure," "Intervention," "Mental Disorders," "Randomised Control Trial." The systematic review report was reviewed critically to ensure that all PRISMA steps and items were included. Nine articles met the inclusion criteria. The choice of programs and methods of intervention may vary depending on the specific mental disorders and individual needs of adolescents. Nursing interventions, including cognitive behavioral therapy, mindfulness-based interventions, group therapy, support groups, and school-based programs, are widely used to manage and treat mental health disorders with the aim of improving well-being and recovery. The effectiveness of intervention programs varies, and selection should consider adolescent needs, resources, and cultural contexts. Consulting mental health professionals or organizations is recommended.